HEMATOLOGICAL-RELATED MALIGNANCY-INDUCED EOSINOPHILIC DERMATOSIS (HE REMAINED): SEBUAH LAPORAN KASUS DERMATOSIS EOSINOFILIK TERKAIT LEUKIMIA LIMFOSITIK KRONIS (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2023)
Introduction: Hematological-related malignancy-induced eosinophilic dermatosis or He Remained is a rare paraneoplastic cutaneous reaction particularly associated with various hematological malignancies. It has a vast clinical presentation ranging from papules, plaque, to blisters and bullae and resembles other dermatoses. We report a case of He Remained on patient with chronic lymphocytic leukimia on remission. Case: A 49-year-old women who had been diagnosed with chronic lymphocytic leukimia presented with a pruritic rash which had been present for a month. Histopathology examination revealed eosinophilic infiltrate and the diagnosis of He Remained was established. She was treated with systemic steroid and achieve relieve of symptoms. Discussion: The pathogenesis of the dermatosis has not been fully interpreted. The cutaneous symptoms have been found to be unrelated to the hematologic malignancy course. Histopathology studies have an important role as one of the diagnostic criteria. Various treatments have obtained some response in short term; however treatments to control the chronic and relapsing course of the disease has been lacking. Conclusion: He Remained has a negative impact for patients and remains a diagnostic and therapeutic challenge for Dermatovenereologist. This case reports hopes to raise awareness given the rarity of the dermatoses.